Clinical Significance of an m6A Reader Gene, IGF2BP2, in Head and Neck Squamous Cell Carcinoma - Deng, Xiaoli; Jiang, Qingshan; Liu, Zhifeng; Chen, Wen (Frontiers in Molecular Biosciences, 2020)
Purpose: The importance of N6-methyladenosine (m6A) in tumor recurrence and prognosis has gradually emerged in recent years. The role of IGF2BP2 as one of m6A readers in regulating HNSCC is not clear. We assessed the prognostic role of IGF2BP2 in HNSCC using openly obtainable information from The Cancer Genome Atlas (TCGA). Materials and methods: We used The Cancer Genome Atlas database in conjunction with HNSCC patients sample IHC（n=36）to analyze the expression of IGF2BP2 in HNSCC. Then we used KS test, logistic regression and Forest Map Analysis to find the correlation between IGF2BP2 expression and clinical characteristics. We assessed the role of IGF2BP2 in prognosis by Kaplan-Meier curves and Cox analysis. Finally, we use TCGA data to explore possible carcinogenic mechanisms with multi-GSEA (Gene set enrichment analysis). Results: Analysis of TCGA data and IHC results showed that IGF2BP2 was upregulated in HNSCC, and the expression level was related to T stage. simultaneously， Kaplan-Meier curves and Cox analysis implicated that highly expressed IGF2BP2 correlated with poor prognosis, and IGF2BP2 was an independent risk factor for HNSCC. Gene set enrichment analysis showed that Scavenging and degradation, Synthesis and metabolism, Cell growth, death and motility and Cancer pathways and Others are differentially enriched in IGF2BP2 high-expression phenotype. Conclusion: Our results show that IGF2BP2 plays an important role in tumor progression and may become an important biological prognostic factor for head squamous cell carcinoma.